Analysis of Th and U breeding in a heat pipe cooled traveling wave reactor - Ma, Kunfeng; Hu, Po (Frontiers in Energy Research, 2023)
Introduction: Heat pipe cooled traveling wave reactor (HPTWR) is a newly proposed heat pipe reactor. The HPTWR can achieve the low enrichment of loaded fuel, small reactivity swing, and long-term continuous operation for the power supply of decentralized electricity markets. Due to the excellent breeding capability of the HPTWR, the Th fuel is also added into the breeding fuel region of the reactor to achieve the Th-U fuel cycle in this work. Methods: The Monte Carlo code RMC is used to obtain the reactivity swing, propagation of axial power peak, burnup, and productions of bred fissile nuclides for the HPTWR with Th and U fuels. Results and Discussion: The results indicate that the HPTWR with 13.6% 235U enrichment of ignition fuel and 20% 235U enrichment of breeding fuel can continuously operate for 18.1 years without refueling when the mass fraction of 232Th in heavy metals of breeding fuel region is 33%. The propagation velocity of axial power peak and total burnup for the HPTWR with Th and U fuels is about 0.5525 cm/years and 24.72 GWd/THM during the 18.1 years operation respectively. The corresponding productions of bred 239Pu, 241Pu and 233U are about 212.99 kg of 239Pu, 0.19 kg of 241Pu and 81.58 kg of 233U at the end of cycle (EOC) respectively. The obtained results in this study demonstrate that the HPTWR can achieve the Th fuel breeding in the case of the low 235U enrichment loading (≤ 20%).